Hubungan Perilaku dan Faktor Penyebab Penggunaan Antibiotik Tanpa Resep di Kalangan Mahasiswa Universitas Tadulako - Tri Randy Saputra; Amelia Rumi; Ririen Hardani (Jurnal Health Sains, 2021)
Behavior and causal factors affect the rate of antibiotic use without a prescription because self-medicating efforts require the extent to which students' understanding of antibiotic use is good and also correct. The purpose of this study is to find out the behavior of non-prescription antibiotic use among tadulako university students, to find out the causative factors of antibiotic use without prescription among tadulako university students, to find out the relationship of behavior and causative factors of antibiotic use without a prescription among tadulako university students and to find out what antibiotics are most consumed without a prescription among tadulako University students. This study used a descriptive method with a cross-sectional approach with 396 respondents. The sampling technique in this study, namely using purposive sampling data collection using questionnaires in Google Form. The results found that the most widely used antibiotic is amoxicillin. Behavior variables are classified as sufficient categories of (63%). Variable causal factors fall into a sufficient category of (66%). Variable level of causal factors that fall into the category of good assessment, namely sub-variables ease of obtaining antibiotics. When viewed by age, gender and class have sufficient knowledge. In conclusion, the results of the chi-square test obtained a value of 0.000 < 0.05 which means there is a significant relationship between behavior and factors causing antibiotic use without a prescription among tadulako university students.